Normal Development of Voice - Pedersen, Mette (Springer Nature, 2024)
This fully revised and extended second edition provides a comprehensive, most up-to-date overview of the investigation of quantitative measurement in the complex of voice. Important objective parameters of normal voice development are assessed, especially relevant when pathological deviations have to be recognized and defined. The description of different qualities of normal voice development in terms of measurable parameters is provided. The book highlights the hormonal changes that have a considerable influence on the physical development of boys and girls, and how it is possible to predict the voice transition statistically. The extent to which hormones affect voice development in the two genders are made clear in this work through the observation of a number of parameters. In this second edition, the focus is extended to include High-Speed Video images and further discussion. Possible interesting topics for further research are also emphasized. This book will be a valuable resource for laryngologists, phoniatricians, and teachers in their daily work. This is an open access book. ; The technical measurement of individual parameters in an area as complex as music and song has achieved acceptance only in recent years. However important objective parameters of normal voice development may be, they are especially so when patholo- cal deviations have to be recognised and defined. It is nevertheless also possible to a certain extent to describe different qualities of normal voice development in terms of measurable parameters. Hormonal changes have a considerable influence on the ph- ical and mental development of boys and girls. The extent to which this influence affects voice development in the two sexes will be made clear in this work through the observation of a number of parameters. I hope that this will stimulate further investigations of this topic. Possible interesting topics for further research are emphasised in the text. Working with adolescents and documenting their vocal dev- opment has given me a lot of pleasure. Colleagues with different medical specialities have supported me in this task. The practical significance of this work has shown itself in the way the results obtained (the graphs and tables) are used today by laryngo- gists, phoniatricians and music teachers in their daily work, and vii viii Preface the determination of hormonal levels in the course of puberty has been introduced as a routine in choirs.